2019
DOI: 10.3390/su11072070
|View full text |Cite
|
Sign up to set email alerts
|

Belt and Road Initiative and Railway Sector Efficiency—Application of Networked Benchmarking Analysis

Abstract: In recent years, there has been a lot of attention paid to China’s Belt and Road Initiative (BRI), which aims to invest in better connecting China, South-East Asia, Central Asia, the Middle East and Europe. As countries that share the same continent, and are in many cases without proper sea connection (landlocked), the key mode of long-distance transportation is railways. However, numerous countries have different levels of past investments, labor productivity, transportation profile, and culture surrounding r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 39 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…Pan Sukun found that communication infrastructure is a non negligible factor affecting China's investment location choice in developed countries along the line. At the same time, he pointed out that the quality of the system and the location choice of OFDI have a regulatory effect [13]. Li Jianjun believes that location selection is the first factor to be considered in China's investment decision-making, and uses panel data to analyze the impact of the institutional quality of the target country and the institutional quality distance between the target country and the home country on China's OFDI location selection [14].…”
Section: Related Workmentioning
confidence: 99%
“…Pan Sukun found that communication infrastructure is a non negligible factor affecting China's investment location choice in developed countries along the line. At the same time, he pointed out that the quality of the system and the location choice of OFDI have a regulatory effect [13]. Li Jianjun believes that location selection is the first factor to be considered in China's investment decision-making, and uses panel data to analyze the impact of the institutional quality of the target country and the institutional quality distance between the target country and the home country on China's OFDI location selection [14].…”
Section: Related Workmentioning
confidence: 99%
“…Extant literature has examined the effect of FDI on host countries through various perspectives. Some scholars have examined the impact of FDI on host countries' productivity [48,49], de-industrialization [50,51], and economic growth [38], while others have investigated the influence of FDI on the institutional quality of host countries and tried to disentangle the mechanisms behind it [3].…”
Section: Theories Of Institutional Effect Of Fdimentioning
confidence: 99%
“…While the B&R initiative encompasses many areas of economic integration and global governance [35], it is specifically an infrastructure-led economic integration plan for integrating China's trading partners by developing their infrastructure (i.e., ports, roads, airports, railways, etc.,).The initiative manifests a Chinese commitment to investing in a variety of infrastructure projects in order to strengthen the economic capacity and connectivity among the B&R countries [36]. In the recent past scholars have paid considerable attention to this initiative which has specifically aimed to invest in better connecting Europe, Middle East, Central Asia, South-East Asia, and China [37][38][39][40]. Along with economic integration the B&R initiative is also considered as a vehicle toward sustainable development [41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…With Pivot, Clarke (2016) analyzes the opportunities and challenges of Eurasia China. While the study of Li and Hilmola (2019) is more of a literature review study related to One Belt One Road.…”
Section: Introductionmentioning
confidence: 99%